ANALISIS PENGGUNAAN INSTAGRAM SEBAGAI MEDIA KOMUNIKASI PEMASARAN ONLINE (STUDI DESKRIPTIF PADA AKUN @beautyhijab.sukoharjo) - Puspita Sari, Dela; Purwo Saputro, Edy; Purworini, Dian; Azaria Rahmadiva, Lelita (Linimasa : Jurnal Ilmu Komunikasi, 2025)
This study aims to determine and describe the use of Instagram as an online marketing communication media carried out by @beautyhijab.sukoharjo, in this study using the AIDA theory (Attention, Interest, Desire, Action), this study uses a descriptive qualitative approach, with data collection through interviews, observations and documentation of 2 people and documentation of the @beautyhijab.sukoharjo account, this study uses a purposive sampling sample with the criteria of the owner and admin of Instagram @beautyhijab.sukoharjo who have an understanding and participate in the process of managing Instagram as an online marketing communication media @beautyhijab.sukoharjo. the results of this study indicate that the use of Instagram is very effective in promoting @beautyhijab.sukoharjo products by implementing marketing communication strategies and applying the AIDA theory through the stages of Attention, Interest, Desire and Action @beautyhijab.sukoharjo can attract consumer attention to products through attractive offers until consumers take action to purchase products.